Magnetic Control of MOF Crystal Orientation and Alignment. Issue 62 (4th October 2017) - Cheng, Fei; Marshall, Ellis S.; Young, Adam J.; Robinson, Peter J.; Bouillard, Jean‐Sebastien G.; Adawi, Ali M.; Vermeulen, Nicolaas A.; Farha, Omar K.; Reithofer, Michael R.; Chin, Jia Min
Abstract: Most metal‐organic frameworks (MOFs) possess anisotropic properties, the full exploitation of which necessitates a general strategy for the controllable orientation of such MOF crystals. Current methods largely rely upon layer‐by‐layer MOF epitaxy or tuning of MOF crystal growth on appropriate substrates, yielding MOFs with fixed crystal orientations. Here, the dynamic magnetic alignment of different MOF crystals (NH2 ‐MIL‐53(Al) and NU‐1000) is shown. The MOFs were magnetized by electrostatic adsorption of iron oxide nanoparticles, dispersed in curable polymer resins (Formlabs 1+ clear resin/ Sylgard 184), magnetically oriented, and fixed by resin curing. The importance of crystal orientation on MOF functionality was demonstrated whereby magnetically aligned NU‐1000/Sylgard 184 composite was excited with linearly polarized 405 nm light, affording an anisotropic fluorescence response dependent on the polarization angle of the excitation beam relative to NU‐1000 crystal orientation. Abstract : Magnetic attraction : Free‐standing NH2 ‐MIL‐53(Al) and NU‐1000 metal‐organic framework (MOF) crystals were magnetized by electrostatic adsorption of iron oxide nanoparticles onto their surfaces, and then magnetically aligned in different fluid matrices. MOF/polymer composites with aligned MOF crystals were prepared, and the importance of crystal orientation on MOF functionality was demonstrated using aligned NU‐1000/Sylgard 184, which showed anisotropic fluorescence response to linearly polarized excitation. This general strategy for controlling MOF crystal orientation will open up new avenues for exploiting anisotropic MOF properties.